1999
DOI: 10.1017/s0012162299001528
|View full text |Cite
|
Sign up to set email alerts
|

Bone age and linear skeletal growth of children with cerebral palsy

Abstract: The aim of this study was to compare the linear growth of children with cerebral palsy (CP) with that of children without CP. The segmental lengths (humerus, ulna, femur, tibia, and spine), recumbent length, body weight, and bone age of 62 children with CP (age range 2.25 to 14 years, mean 7.13 years) were measured and compared with 68 children without CP (age range 1.50 to 12.67 years, mean 6.73 years). The results show that bone-age delay is common in children with CP (68% with a delay of more than 1 year). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 14 publications
2
20
2
Order By: Relevance
“…But the fact that we have studied patients with hemiplegia, in which the normal side was the control group, and the fact that we have also observed a delay in the affected side compared to the unaffected, not only corroborates this statement, but we can also correlate with the involvement of non-nutritional factors 6 8 , 9 , 11 , 12 …”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…But the fact that we have studied patients with hemiplegia, in which the normal side was the control group, and the fact that we have also observed a delay in the affected side compared to the unaffected, not only corroborates this statement, but we can also correlate with the involvement of non-nutritional factors 6 8 , 9 , 11 , 12 …”
Section: Discussionsupporting
confidence: 67%
“…Even so, tetraparetic patients showed a longer development delay, and this may be related to nutritional and non-nutritional factors 6 7 , 9 - 11 , 13 , 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct measurement of height to quantify a growth spurt in children with CP is often difficult or even impossible, due to contractures, skeletal deformities, or inability of the child to stand erect. Kong et al 4 found a strong association between skeletal age and linear skeletal growth in children with CP, and recommended that skeletal age with reference to the child’s own chronological age should be used to describe growth. A reliable and simple method that can be used to measure skeletal age in growing children is the Greulich and Pyle technique 5–7 .…”
mentioning
confidence: 99%
“…Skeletal growth abnormalities in children with CP have been found in several studies 4,8–11 . However, the data are conflicting; some reported a delayed skeletal age in children with CP, 4,10 while others reported a normal, 8,11 or even an advanced skeletal age 9 . The majority of these studies have focused on children with severe CP, most of whom were non‐ambulant 4,8,11 .…”
mentioning
confidence: 99%